2022
DOI: 10.1088/1361-6560/ac8ddd
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric impact of intrafraction motion under abdominal compression during MR-guided SBRT for (Peri-) pancreatic tumors

Abstract: Objective – Intrafraction motion is a major concern for the safety and effectiveness of high dose stereotactic body radiotherapy (SBRT) in the upper abdomen. In this study, the impact of the intrafraction motion on the delivered dose was assessed in a patient group that underwent MR-guided radiotherapy for upper abdominal malignancies with an abdominal corset. Approach – Fast online 2D cine MRI was used to extract tumor motion during beam-on time. These tumor motion profiles were combined with linac log files … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…They concluded that there was no correlation between respiratory movement and dosimetry impact. Still, they advised that this represents a limited view of the respiratory cycle and does not consider larger respiratory cycles [27]. Therefore, we still perform DIBH in the thorax and upper abdominal treatments, and physicists design a robust modulation plan with a time limit of less than 15 min on Beam ON.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that there was no correlation between respiratory movement and dosimetry impact. Still, they advised that this represents a limited view of the respiratory cycle and does not consider larger respiratory cycles [27]. Therefore, we still perform DIBH in the thorax and upper abdominal treatments, and physicists design a robust modulation plan with a time limit of less than 15 min on Beam ON.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic body radiotherapy (SBRT) has been used successfully for the treatment of unresectable upper abdominal malignancies (1)(2)(3)(4)(5)(6). Compared with conventional 3-dimensional conformal radiotherapy or intensity-modulated radiotherapy, SBRT offers highly precise and accurate treatment through the delivery of high radiation doses to tightly de ned target areas in small numbers of fractions.…”
Section: Introductionmentioning
confidence: 99%
“…This motion trace was characterized by its respiratory motion amplitude and maximum drift in the same manner as in our previous studies. 61,107 The respiratory amplitude was calculated by high-pass filtering the motion trace and calculating the peak-to-peak distance, and the drift magnitude was calculated by low-pass filtering and extracting the maximum absolute value of the drift motion. The overall respiratory amplitude and drift were calculated as the 2-norm of their values in the three cardinal directions: cranio-caudal (CC), anterior-posterior (AP ), and left-right (LR).…”
Section: Dose Reconstructionmentioning
confidence: 99%
“…Mitigating respiratory motion with passive motion management, like abdominal compression, is a wellestablished method in the upper abdomen, 33, 61, 66, 92-95 but residual motion and small drifts can still have a significant dosimetric impact on target coverage and OAR dose. 83,[105][106][107] Online motion monitoring in the upper abdomen is challenging due to the limitations of contemporary MRI techniques. In order to capture detrimental breathing irregularities and tumor drifts, imaging ideally needs to be conducted in a time-resolved fashion, at a frequency fast enough to capture respiratory motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation